EFFICIENCY OF BPRS IN INDONESIA USING TWO STAGES METHOD - DATA ENVELOPMENT ANALYSIS (DEA) - Ratih Nur Cahyati; Ulfi Kartika Oktaviana (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2025)
The efficiency of BPRS in Indonesia is very important in supporting MSMEs, but the performance of BPRS is often constrained by internal financial conditions and external economic factors, raising concerns about its level of efficiency. This study aims to examine the efficiency of BPRS in Indonesia and the factors that influence it. This study uses a quantitative method with a Two-Stage DEA approach and time series data sourced from financial reports for the period 2014 to 2023. The first-stage analysis shows that BPRS in Indonesia is still in an inefficient condition. In the second stage, the Tobit regression results indicate that ROA, FDR, and NPF significantly affect the efficiency of BPRS in Indonesia, while CAR and BI Rate do not have a significant impact. These findings emphasize the importance of BPRS in improving asset management and risk control to enhance efficiency and strengthen its role in supporting the Islamic financial system.